The Effects of Automation and Technology on Employment and Job Displacement (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
This article examines the profound effects of automation and technology on employment and job displacement. As technology continues to advance at an unprecedented pace, the impact on the labor market has become a topic of significant concern and interest. The annotation explores the various ways in which automation and technology influence employment, both positively and negatively, and delves into the implications for workers, businesses, and society as a whole.